Cross-Protective Shigella Whole-Cell Vaccine With a Truncated O-Polysaccharide Chain - Kim, Min Jung; Moon, Young-hye; Kim, Heejoo; Rho, Semi; Shin, Young Kee; Song, Manki; Walker, Richard; Czerkinsky, Cecil; Kim, Dong Wook; Kim, Jae-Ouk (Frontiers in Microbiology, 2018)
Shigella is a highly prevalent bacterium causing acute diarrhea and dysentery in developing countries. Shigella infections are treated with antibiotics but Shigellae are increasingly resistant to these drugs. Vaccination can be a countermeasure against emerging antibiotic-resistant shigellosis. Because of the structural variability in Shigellae O-antigen polysaccharides (Oag), cross-protective Shigella vaccines cannot be derived from single serotype-specific Oag. We created an attenuated Shigella flexneri 2a strain with one rather than multiple Oag units by disrupting the Oag polymerase gene (Δwzy), which broadened protective immunogenicity by exposing conserved surface proteins. Inactivated Δwzy mutant cells combined with Escherichia coli double mutant LT(R192G/L211A) as adjuvant, induced potent antibody responses to outer membrane protein PSSP-1, and type III secretion system proteins IpaB and IpaC. Intranasal immunization with the vaccine preparation elicited cross-protective immunity against S. flexneri 2a, S. flexneri 3a, S. flexneri 6, and Shigella sonnei in a mouse pneumonia model. Thus, S. flexneri 2a Δwzy represents a promising candidate strain for a universal Shigella vaccine.